Discovery Learning Model and WEB-Based Interactive Media: Its Impact on Student Academic Performance - Ayis Crusma Fradani; Rika Pristian Fitri Astuti; Reni Safitri (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
The improvement of the quality of education for the younger generation is greatly influenced by effective and innovative education. This study aims to analyze the impact of the application of the Discovery Learning model combined with web-based interactive media on students' academic performance in the era of digital learning. The study used a quantitative approach involving 38 tenth-grade students as samples. Data was collected through pre and post-tests of the model and media application, then statistically analyzed. The results showed a significant increase in the average student score from 50.92 (pretest) to 85.52 (posttest). Hypothesis testing showed a significance value of 0.000 (< 0.05), confirming that the combination of Discovery Learning and web-based media is effective in improving student academic performance. This model encourages students to be more active, independent, and engaged in the learning process, while web-based media creates an interesting, interactive, and easily accessible learning experience. Therefore, this combination is highly recommended for use in modern education to improve overall educational quality.